1990
DOI: 10.1136/adc.65.12.1319
|View full text |Cite
|
Sign up to set email alerts
|

Increasing asthma prevalence in a rural New Zealand adolescent population: 1975-89.

Abstract: A survey of asthma symptoms and spirometry in 435 adolescent schoolchildren was undertaken in 1989 in a rural, largely Maori population. The survey questionnaires were identical to those used in a 1975 survey at the same school. The prevalence of reported asthma or wheeze significantly increased from 26*2% to 3400%. This increase occurred in groups reporting asthma, and also those reporting wheeze unassociated with colds, but without a previous diagnosis of asthma. There was a tendency for a rise in reported w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
2
9

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 7 publications
5
53
2
9
Order By: Relevance
“…Hot and humid climates (characteristics that Recife has) are associated with greater prevalence. 24 The reduction in asthma prevalence reported in Recife differs from international studies, 10,11,[15][16][17] in which the opposite has occurred. In Brazil results are divergent.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Hot and humid climates (characteristics that Recife has) are associated with greater prevalence. 24 The reduction in asthma prevalence reported in Recife differs from international studies, 10,11,[15][16][17] in which the opposite has occurred. In Brazil results are divergent.…”
Section: Discussioncontrasting
confidence: 48%
“…In Melbourne, the prevalence of reported asthma increased for the 7 year-old subset from 19.1 to 46% between 1964 and 1990. 16 Shaw et al, 17 studying adolescents in New Zealand observed an increase in the prevalence of reported asthma or wheezing from 26.2 to 34.0%, in the period from 1975 to 1989.…”
Section: Introductionmentioning
confidence: 99%
“…BRABÄCK et al [15], in a comparison of atopic sensitization and respiratory symptoms among Swedish and Polish school children, reported that children living in urban Sweden, as compared to urban Poland, were more frequently diagnosed as being asthmatic by a doctor, and had higher prevalences of positive skin-prick test reactions against mugwort, timothy, birch and cat. Several studies have indicated a rising trend in atopic diseases and asthma over time both in children [16][17][18][19][20][21] and adolescents [2,22,23]. Most authors suggest that this is not simply due to improved diagnostic trends.…”
Section: Discussionmentioning
confidence: 99%
“…Dois estudos realizados com intervalo de 12 anos (1975 e 1987) identificaram aumento de 26,2% para 34% na prevalência de asmáticos entre adolescentes dessa população. Etnia, aumento do tabagismo materno e redução das infecções respiratórias durante a infância precoce foram apontados como possí-veis justificativas para o fato (20) . Já na Alemanha, um estudo avaliando crianças e adolescentes de duas cidades situadas no Oeste e no Leste encontrou prevalência maior de asmáticos na região ocidental do país.…”
Section: J Pneumol 27(5) -Set-out De 2001unclassified